A treatment of expansive soil using different additives - Fattah, M.Y.; Salman, F.A.; Nareeman, B.J. (The Technical University of Košice, 2010)
There are many factors that govern the expansion behavior of soil. The primary factors are a change in water content and the amount and type of clay size particles in the soil. Other important factors affecting the expansion behavior include the type of soil (natural or fill), condition of the soil in terms of dry density and moisture content, magnitude of the surcharge pressure, and amount of no expansive material such as gravel or cobble size particles. In this paper, a swelling soil from the site Hamamuk earth dam, which is located in Koya town north of Iraq, is treated by four types of additives; cement, steel fibers, gasoline fuel and injection by cement grout. The treatment of the expansive soil with 5 % of cement or steel fibers or the injection with cement grout revealed a better improvement while 4 % of gasoline oil is sufficient to reveal the optimum treatment by this material. The angle of internal friction is not affected by the treatment while the cohesion between particles is slightly affected by these additives due to a change in the adhesion between the additive and soil particles.